2019
DOI: 10.18632/oncotarget.26906
|View full text |Cite
|
Sign up to set email alerts
|

Sustained partial remission of a metastatic NEN using off-label immunotherapy with pembrolizumab

Abstract: Neuroendocrine neoplasms (NEN) are a heterogeneous group of tumors, which can be histologically separated by primary location, proliferation rate and differentiation of tumor cells. The therapeutic options and outcome depend on grading, staging and resectability of the tumor. Established treatment options of neuroendocrine tumors (NET) and carcinomas (NEC) are based especially on surgery, tumor specific medical treatments, peptide guided radioreceptor therapy (PRRT) and locoregional therapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We have already reported [ 34 ] about a 55-year-old male patient, who was diagnosed with a non-functional SSR-positive NET G2 of the pancreatic tail with invasion of the spleen and synchronous SSR negative bilobar liver metastases, which progressed into a NEC (Ki-67 > 50%) with additional metastasis to kidney, adrenals, peritoneum, and lymph nodes.…”
Section: Individual Case Presentationmentioning
confidence: 99%
“…We have already reported [ 34 ] about a 55-year-old male patient, who was diagnosed with a non-functional SSR-positive NET G2 of the pancreatic tail with invasion of the spleen and synchronous SSR negative bilobar liver metastases, which progressed into a NEC (Ki-67 > 50%) with additional metastasis to kidney, adrenals, peritoneum, and lymph nodes.…”
Section: Individual Case Presentationmentioning
confidence: 99%
“…If so, this might also explain why first clinical trials with checkpoint inhibitors in NEN failed but significant benefit has been reported in individual patients. Incidentally, one of the patients with high FLT3LG tissue mRNA expression benefited substantially from treatment with a checkpoint inhibitor started 13 months after surgery [22]. In addition, high circulating Flt3L was detected in a blood sample of this patient obtained during the remission phase that followed treatment initiation.…”
Section: Discussionmentioning
confidence: 89%
“…While much-anticipated first clinical trials with immune checkpoint inhibitors in NEN have been disappointing [17], subgroup analyses have suggested more favorable response profiles in high grade NEN [18,19]. Furthermore, a growing number of case reports suggest that individual patients benefit substantially [20][21][22], creating an urgent need to better understand NEN immune control and evasion, especially in patients with advanced aggressive disease, who have otherwise run out of established therapeutic options [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of activity of PD-1/PD-L1 immune checkpoint inhibition are mainly reported in NECs [89][90][91]. The phase II spartalizumab trial also includes a cohort of patients with well-differentiated gastrointestinal (N = 30) and pancreatic NET (N = 30) and a cohort of patients with poorly differentiated GEP-NEC (N = 20).…”
Section: Immunotherapy In Gastroenteropancreatic Nensmentioning
confidence: 99%